Carotenoids New Perspectives and Application - María Martínez-Espinosa, Rosa (Physiology, 2022)
Carotenoids are natural and versatile secondary metabolites, most of them showing colours that vary from yellow to red. They are widespread among living beings where they are involved in many biological roles reporting beneficial actions. To date, more than 750 carotenoids have been described in nature. Humans cannot synthesize carotenoids de novo, thus they are mainly obtained through diet. In fact, carotenoids are consistently found in tissues or biological fluids where they play a beneficial decreasing the risk of developing some diseases.During the last half-century, significant advances in carotenoids research have been made. This book highlights new perspectives and applications of carotenoids including characterization and isolation of new compounds (including rare carotenoids), their production at a mid-large scale (involving new innovative approaches), and uses of carotenoids in different biotechnological fields like food science, biomedicine, and cosmetics.